2014
DOI: 10.1111/pme.12262
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Radiofrequency Neurotomy Reduces Central Hyperexcitability and Improves Neck Movement in Individuals with Chronic Whiplash

Abstract: Attenuation of psychophysical measures of augmented central pain processing and improved cervical movement imply that these processes are maintained by peripheral nociceptive input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 96 publications
7
78
1
Order By: Relevance
“…14,17,19,26 Treatments targeting facetogenic pain are available. Radiofrequency neurotomy interventions, which denervate the multifidus muscle, have been shown to attenuate the psychophysical signs/symptoms of whiplash (eg, reduced thermal/pressure pain thresholds) 21 and low back pain. 3 However, considering the known resolution of facetogenic pain, the long-term consequences of radiofrequency neurotomy on the structure and function of the deep cervical muscles (and lumbar muscles 3,22 ) are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,19,26 Treatments targeting facetogenic pain are available. Radiofrequency neurotomy interventions, which denervate the multifidus muscle, have been shown to attenuate the psychophysical signs/symptoms of whiplash (eg, reduced thermal/pressure pain thresholds) 21 and low back pain. 3 However, considering the known resolution of facetogenic pain, the long-term consequences of radiofrequency neurotomy on the structure and function of the deep cervical muscles (and lumbar muscles 3,22 ) are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included studies, 12 reported reflex threshold (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015), six reported reflex peak magnitude or AUC or both Avramidis et al, 1998;De Marinis et al, 2007;Peddireddy et al, 2009;Rhudy et al, 2013;Kofler and Halder, 2014), six reported reflex latency (Avramidis et al, 1998;Katsarava et al, 2004;De Marinis et al, 2007;Courtney et al, 2009;Peddireddy et al, 2009;Kofler and Halder, 2014), and two reported reflex duration (Courtney et al, 2009;Peddireddy et al, 2009). Pain populations included 'chronic pain', migraine, migraine without aura, tension type headache, chronic tension type headache, fibromyalgia, rheumatoid arthritis, chronic upper back pain, chronic low back pain, knee osteoarthritis, chronic whiplash associated disorder, irritable bowel syndrome, chronic lateral epicondylalgia ('tennis elbow'), and a combination of idiopathic pain, myofascial pain, and headache (see Table 1 for study details).…”
Section: Included Studiesmentioning
confidence: 99%
“…Two studies investigated two patient groups (Rhudy et al, 2013;Smith et al, 2013), which increased our group comparisons to 15. Pain groups had an overall lower reflex threshold than controls, with a large effect size [− 0.83 (95% CI, −1.18 to −0.47), p < 0.0001] (see Figure 2).…”
Section: Reflex Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the small sample and lack of reproduction, this pair of papers has had considerable impact on the practice of interventional medicine for chronic WAD. 66,115 More recently, Smith and colleagues 94,95 used a robust set of secondary outcomes in a noncontrolled observational cohort study (n = 46) to find similar temporal relationships between concomitant reduction (and subsequent return) of chronic WAD-related pain and psychological distress. 95 While it is difficult to draw definitive conclusions from a small body of knowledge, the existing data suggest that 40% to 45% of people with chronic WAD may indeed have symptoms originating from a peripheral articular lesion and that, in some, these painful lesions may cause affective distress.…”
Section: Prior Knowledge Pathoanatomical Lesionsmentioning
confidence: 99%